Pengaruh Persentase Alkali pada Serat Pangkal Pelepah Daun Pinang (Areca Catechu) terhadap Sifat Mekanis Komposit Polimer - Betan, Agustinus Deka; Soenoko, Rudy; Sonief, Achmad AsÂ´ad (Rekayasa Mesin, 2014)
The community of NTT has used betel tree (Areca Catechu), especially for its base of betel leaf, as a burning material for cooking, as a rope to tie the house roof made from bamboo, and as a device to peel traditional candlenut. Economic value of betel is not high, therefore, the fiber of betel tree as a material to empower the polymer matrix composite was need to be optimized. Betel fiber-based composite is expected to be used as the substitute of concrete brick, red brick, triplex, and cloth hanger because of the favorable mechanical characteristics such as strong, light, environmental friendly, resistant to bending, resistant to water, resistant to heat, and economic. Natural fiber-based composite, especially which is made from betel fiber, has low strength so that chemical treatment is needed. NaOH (alkali) was commonly used as chemical. In this study NaOH is given at different percentage for each fiber. The selected percentages in this experiment are 4%, 5% and 6% NaOH. Result of experiment shows that the highest tensile strength of fiber is found at 5 % NaOH which rates for 195 MPa.Keywords: Areca Catechu, Alkali Percentages, Mechanical Properties